{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

hw9sol

# Y1t ht f1t ht t 15t 1 ht 15ht 1

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: e function is shifted. y1(t) = h(t) ∗ f1(t) =h(t) ∗ (δ(t)-1.5δ(t − 1)) = h(t) – 1.5h(t − 1) = [2u(t − 1) + u(t − 2) − 2u(t − 3) − u(t − 5)]- 1.5[2u(t − 2) + u(t − 3) − 2u(t − 4) − u(t − 6)] y1(t) =2u(t − 1) -2u(t − 2) – 3.5u(t - 3)+ 3u(t − 4)− u(t − 5) +1.5u(t − 6) 2 1 0 y1(t) -1 -2 -3 -4 0 1 2 3 t 4 5 6 7 Page 5 / 11 ECE 202 HW solution #9 for prob. 33~36 Prof. DeCarlo (ii) f2(t) = u(t)-1.5u(t − 1) y2(t) = h(t) ∗ f2(t) =h(t)*[u(t)-1.5u(t − 1)] =[2u(t − 1) + u(t − 2) − 2u(t − 3) − u(t − 5)] *[u(t)-1.5u(t − 1)] = 2r(t − 1) + r (t − 2) − 2 r (t − 3) − r (t − 5)- 3r(t − 2) - 1.5r (t − 3) + 3r (t − 4) + 1.5r (t − 6) y2(t)= 2r(t − 1) -2r (t − 2) – 3.5 r (t − 3) + 3r (t − 4) -r (t − 5) +1.5 r (t − 6) 2 1 0 y2(t) -1 -2 -3 -4 0 1 2 3 t 4 5 6 7 (iii) f3(t) = h(-t)=u(t + 5 ) + 2u(t+3) − u(t + 2) −2 u(t +1) y3(t) = h(t) ∗ f3(t) =[2u(t − 1) + u(t − 2) − 2u(t − 3) − u(t − 5)] * [u(t + 5 ) + 2u(t+3) − u(t + 2) −2 u(t +1)] =2r(t + 4) + r(t + 3) – 2r(t + 2) − r(t) + 4r(t + 2) + 2r...
View Full Document

{[ snackBarMessage ]}